ANALYSIS OF COMPETENCY AND JOB SATISFACTION ON THE PERFORMANCE OF WAREHOUSE STAFF IN LOGISTICS COMPANIES IN JAKARTA - Susanto , Primadi Candra; Sawitri , Ni Nyoman; Ali , Hapzi; Rony, Zahara Tussoleha (International Conference on Humanity Education and Society (ICHES), 2024)
The aim of this research is to see whether there is an influence between competency and job satisfaction and warehouse staff performance, an influence between competency and warehouse staff performance, and an influence between job satisfaction and warehouse staff performance. This research uses quantitative research methods with respondents from logistics companies providing storage for imported goods in North Jakarta, with 48 warehouse staff respondents from five companies who are considered representative as the research population. Data analysis to find the influence of the independent variable on the dependent variable using SPSS data analysis software using linear regression with appropriate interpretation results from the processed questionnaire data. The findings from this research are that all statements in the research indicators are declared valid and the results of this research are that there is a relationship between the independent variables and the dependent variable. Paper results This prove that No There is influence significant and positive between variable Competence with Job Performance Variables Warehouse Staff , besides neither does that There is influence positive and significant between Satisfaction Work with Work Performance Warehouse Staff . But other results show that in a way simultaneous There is influence positive and significant between third variable . Recommendation This for the company created object in paper This that need increase competence and prove that necessity improve and show satisfaction Work to party third or consumer .